Comparison of the Diagnostic Performances of Same-session Endoscopic Ultrasound- and Endoscopic Retrograde Cholangiopancreatography-guided Tissue Sampling for Suspected Biliary Strictures at Different Primary Tumor Sites - Seong Jae Yeo (The Korean Journal of Gastroenterology, 2019)
Background/Aims: Determining the cause of suspected biliary stricture is often challenging in clinical practice. We aimed to compare the diagnostic yields of endoscopic ultrasound-guided tissue sampling (EUS-TS) and endoscopic retrograde cholangiopancreatography-guided tissue sampling (ERCP-TS) in patients with suspected biliary stricture at different primary lesions. Methods : We enrolled patients who underwent same-session EUS- and ERCP-TS for the evaluation of suspected biliary stricture. Forceps biopsy and/or brush cytology of intraductal lesions and fine-needle aspiration for solid mass lesions were performed during ERCP and EUS, respectively. Results : One hundred and twenty-five patients treated at our institution between January 2011 and September 2016, were initially considered for the study. However, 32 patients were excluded due to loss of follow-up (n=8) and ERCP-TS on the pancreatic duct (n=20) or periampullary lesions (n=4). Of the 93 patients included, 86 had a malignant tumor including cholangiocarcinoma (n=39), pancreatic cancer (n=37), and other malignancies (n=10). Seven patients had benign lesions. EUS-TS had higher rate of overall diagnostic accuracy than ERCP-TS (82.8% vs. 60.2%, p=0.001), and this was especially true for patients with a pancreatic lesion (84.4% vs. 51.1%, p=0.003). Conclusions: EUS-TS was found to be superior to ERCP-TS for evaluating suspected biliary strictures, especially those caused by pancreatic lesions.